Development of biosensor technology for detecting specific contaminants in environment and agriculture - Abdul Aziz, Azila; Mat Daud, M. Nazri; Kassim, M. Hafiz (Universiti Teknologi Malaysia, 2005)
Biogenic amines such as histamine, cadaverine and putrescine have been confirmed as useful chemical indicators to estimate bacterial spoilage of foods, particularly fish and fish products, cheese, meat and fermented foods. Histamine is toxic at high intakes, while cadaverine and putrescine potentiate the effects of histamine. The regulated level of histamine is 200 mg/kg (200 ppm). For biogenic amines biosensor, the basic principle is the action of diamine oxidase (DAO) that catalyzes the oxidative deamination of primary amines to the corresponding aldehydes, hydrogen peroxide and ammonia. Biogenic amines concentration can be measured by monitoring either the decrease in oxygen or the increase of hydrogen peroxide concentration. Recently, it has been found that DAO from pea seedlings shows higher activity compared to commercial porcine kidney diamine oxidase (PKAO). For that reason, in this research, DAO from Cicer arietinum (chick pea) seedlings will be used to develop the biogenic amines biosensor. Amine oxidases from chick pea (CPAO) was successfully purified following three chromatographic steps, giving a specific activity of 12.7, 11.7 and 0.45 U/mg with putrescine, cadaverine and histamine as substrate, respectively. The molecular mass of the CPAO was 73 kDa, determined by SDS-PAGE. Immobilization of PKAO in crosslinked poly (vinyl alcohol) (PVA) has been performed, and PVA concentration of 10% and cross-linking ratio (CR) of 0.06 were found to be the optimum parameters for CPAO immobilization. Immobilization of partially purified CPAO has also been done. Result showed that at equal enzyme loading, CPAO-PVA membranes gave higher apparent activities compared to commercial PKAO-PVA membranes.